The Development of Wicker Wall Lamp from Talipot Palm Leaves - อนันต์วราพงษ์, อมรรัตน์; หนูแดง, พีรพงษ์; ศรีษะมน, พัสวี; จันทร์สมัคร, ชนาพร (Ratchaphruek Journal, 2018)
ABSTRACT This study aimed to 1) investigate the customers demand on wicker wall lamp, 2) develop wicker wall lamp that answers the customers demand and 3) evaluate the customers’ satisfaction toward the wicker wall lamp from Talipot palm leaves. The four three-dimensional (3D) pattern of wicker wall lamp from Talipot palm leaves were designed. The pattern will be evaluated and used in further step. The participants were five technicians who are expert in manufacturing and product design. Research instrument was open-ended questionnaire. Technicians selected pattern Number 2 because it was the most suitable pattern. The prototype of wicker wall lamp was made and use as the sample in customers’ satisfaction evaluation step. The participants were 50customers who are interesting in wicker wall lamp from Ban Tublan woven group, Prachinburiprovince. The research instrument was customers’ satisfaction questionnaire. The customers’ satisfaction score showed that 1) product design aspect: the customers satisfied the concordant of material and product ( =4.22), 2) usefulness aspect: the customers satisfied the commercial value of product ( =4.42), and 3) the satisfaction toward whole product, the wicker wall lamp gained the customer satisfaction in highest level ( =4.22).